Adjusting democracy indices to the age of mass migration: voting rights of denizens and expats. Issue 4 (8th August 2022) - Altman, David
ABSTRACT: Contemporary migration flows affect virtually all aspects of the social fabric, democracy included. Focused on the competitiveness aspects of the regime, comparative measurements of democracy have underestimated the complexity of the Dahlian dimension of inclusiveness, a sine qua non for defining a polyarchy. This measurement paper proposes a new index of inclusiveness: Electoral Residential Inclusiveness . This measure, an alternative to the most frequently used ethnonational ones, assesses the size of the overlap between those who make the law and those who are subject to it. It is shown how some regimes—including some typically considered strong democracies—exhibit such a considerable gap between these two groups that their democratic credentials could be questioned. Regardless of the new metric's efficacy, one implication of this research is that measures of democracy need to be explicit about the complex normative decisions on how we conceptualize, measure, and aggregate the inclusiveness dimension of polyarchy.